Physiological and biochemical responses of photomorphogenic tomato mutants (cv. Micro-Tom) under water withholding - Rodrigues Alves, Frederico Rocha; Melo, Hyrandir Cabral de; Crispim-Filho, Ailton Jose; Costa, Alan Carlos; Telles Nascimento, Kelly Juliane; Carvalho, Rogerio Falleiros [UNESP] (Springer, 2016)
In addition to mediating photomorphogenesis, phytochromes are responsible for many abiotic stress responses, acting upon biochemical and molecular mechanisms of cell signaling. In this work, we measured the physiological and biochemical responses of phytochromemutant plants under water stress. In tomato (Solanum lycopersicum L.), the aurea mutant (au) is phytochromedeficient and the high-pigment-1 mutant (hp1) has exaggerated light responses. We examined the effects of water withholding on water potential, leaf gas exchange, chlorophyll fluorescence, chloroplast pigment content and antioxidant enzyme activity in au and hp1 and their wildtype cultivar Micro-Tom (MT). Initial fluorescence and potential quantum efficiency of photosystem II (PSII) photochemistry were not affected by the treatment, but effective quantum yield of PSII, electron transport rate decreased and non-photochemical quenching increased significantly in MT. Under water withholding conditions, MT had higher malondialdehyde concentration than the mutants, but au had higher activities of catalase and ascorbate peroxidase compared to the other genotypes. The tolerance of mutants to the effects of water withholding may be explained by the higher activity of antioxidant enzymes in au and by a higher concentration of antioxidant compounds, such as carotenoids, in hp1.
Keywords: Aurea; High-pigment-1; Chlorophyll fluorescence; Antioxidant enzymes